Ultrathin, transparent, flexible, and dual-side white light-responsive two-dimensional molybdenum disulfide quantum disk light-emitting diodes. (June 2022) - Chien, Y.-C.; Shen, T.-L.; Wu, W.-K.; Li, C.-Y.; Chin, H.-T.; Chang, C.-W.; Lin, T.-Y.; Chang, S.-H.; Shen, J.-L.; Chen, Y.-F.
Abstract: Ultrathin, transparent, and flexible devices with multifunctionalities are indispensable for emerging technologies. However, the related reports are very few, and the efficiency is rather limited owing to material restriction and complicated fabrication processes. In this work, a light-responsive white light-emitting diode (LED) with ultrathin, transparency, dual-side emission, and flexible characteristics based on graphene-insulator-semiconductor (GIS) structure is demonstrated. The GIS light-responsive white LED consists of highly luminescent histidine-doped two-dimensional molybdenum disulfide (MoS2 ) quantum disks, an Al2 O3 insulating layer, and a graphene transparent electrode. By applying an external bias, it enables to generate white light emission with a high emission efficiency of around 9%. The underlying mechanism can be well understood by quantum tunneling. In addition, the GIS structure also shows good durability under a bending test of 200 cycles. Unlike conventional white LEDs, which always required multiple emissive layers, our GIS light-responsive LED is only based on a single emissive material of histidine-doped MoS2 quantum disks, which possess a broadband emission property and low toxicity. Therefore, with the superior multiple functionalities, our study shown here is very useful for the future development of next-generation optoelectronic devices. Graphical abstract: Image 1